Re-enacting oedipus rex with Yoruba witticism (2011)
Yoruba proverbs are witty expressions, the effective use of which requires being apt and clever. These traits that dominate the work of Ola Rotimi, The Gods Are Not To Blame, do more than reflecting the Yoruba's perception of the world. Hence, this paper examines how strong opinions, foreboding and misfortunes are conveyed with the Yoruba literary devices to produce Sophoclean emotions. Yoruba Proverbs or witty sayings are demonstrated in this work as very rich in figures of speech and meaning; products of human experiences or relations as well as observation of natural phenomena, which are communicated with words of mouth, songs and talking-drums. These elements constitute the witticism shown in this article as powerfully employed by the playwright who has succeeded in recreating the tragedy of Oedipus Rex in a Yoruba setting, before, as it were, an African audience.